Business Environment in Emerging Market Countries. (May 2021) - Liu, Qian
The business environment of a country or region is an important measure of its economic soft power and an indicator of the strength of its governance. A good business environment attracts foreign investment, which emerging market countries in structural transformation are most concerned about. This article calculates and ranks the business environment index of the 30 emerging market countries (E30). It assesses the trend of the overall business environment and the contributing factors and conducts an empirical analysis of how business environment in these countries affects their economic development. The study shows that the business environment of the E30 countries is closely related to their economic development, albeit with prominent regional differences. Additionally, the quality of business environment is closely related to the strength of government regulation. In the last 5 years, the business environment of the E30 countries has improved in general, and closed the gap with the OECD countries, with Asian countries demonstrating the most conspicuous improvement. Empirical results show that the overall score of the business environment has a significantly positive effect on economic development. Lastly, based on a systematic analysis of the business environment of the E30 countries, the article summarizes the findings and makes projections about future development.